Frankie vs the Pirate Pillagers - Lampard, Frank (London Little Brown Books for Young Readers, 2014)
"Frankie and his friends love playing soccer so much that they start their own team. They can always find time to play a game. But when they win an old soccer ball at a carnival, Frankie's team is going to be transported to a magical world of soccer they never knew existed. Can Frankie and his friends beat the Pirate Pillagers and make their way home?"
Include Illustration
Keywords: Soccer teams